Falencias en la formación de habilidades gerenciales en programas de contaduría en tres universidades colombianas (2012)
This study was made in order to find the possible flaws in the training of managerial skills in three universities in Colombia, through the comparative study of the proposals of experts in the field, with the curriculum and academic programs at universities New Granada, La Salle and the Gran Colombia. The comparative study was done first between the selected authors (Paez, 2005, Manrique, 2004, Sanint, Tafurt, Dorado, Chambers, y Red, 2003), seeking to find a few points in common, to then go to compare to each one of the authors with each of the universities outlined. It is noticeable that the selected universities do not provide a comprehensive plan to train managerial skills to the future public accountants.